2011
DOI: 10.1111/j.1600-0404.2010.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylphenidate and/or levodopa coupled with physiotherapy on functional and motor recovery after stroke - a randomized, double-blind, placebo-controlled trial

Abstract: Ischemic chronic stroke patients having MPH and/or LD in combination with physiotherapy showed a slight ADL and stroke severity improvement over time. Future studies should address the issue of the optimal therapeutic window and dosage of medications to identify those patients who would benefit most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 41 publications
2
47
0
2
Order By: Relevance
“…Our finding that mood recovery is improved by a combined treatment (MPH + LD) accords with the result of a previous investigation in which there was a significant difference in the Barthel Index compared to placebo [29]. It seems that combination therapy may have a widespread effect on ADL and mood recovery by the presence of L -dopa, thereby causing increased dopamine levels.…”
Section: Discussionsupporting
confidence: 81%
“…Our finding that mood recovery is improved by a combined treatment (MPH + LD) accords with the result of a previous investigation in which there was a significant difference in the Barthel Index compared to placebo [29]. It seems that combination therapy may have a widespread effect on ADL and mood recovery by the presence of L -dopa, thereby causing increased dopamine levels.…”
Section: Discussionsupporting
confidence: 81%
“…6 Likewise, clinical studies have shown that the use of pharmacological therapies that increase brain concentrations of brain amines such as dopamine and serotonin promotes a positive impact on stroke outcomes. 7 Moreover, the modulation of serotoninergic neurotransmission by using selective serotonin reuptake inhibitors such as fluoxetine and citalopram improved motor and cognitive recovery in both the clinic 8,9 and the laboratory. 10 Positron emission tomography (PET) with [ 11 C]DASB and [ 18 F]altanserin has widely been used to investigate the availability of serotonin transporter (SERT) and serotonin receptor 5-HT 2A in both humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving levodopa had significant improvement in motor recovery and independent ambulation. Subsequent small studies using levodopa with or without methylphenidate [36] or levodopa with or without amphetamine [37] could not show a difference in motor recovery or improvement in functional outcomes with treatment. An ongoing study which commenced in 2010, has enrolled 572 patients are to receive 100 mg of levodopa and 25 mg of carbidopa, or placebo, 1 hour before physiotherapy.…”
Section: Enhancing Recovery With Special Reference To Walking and Aphmentioning
confidence: 94%